Analisis Performance Elevator Studi Kasus Di Pasar Grosir Tanah Abang (Blok A) Menggunakan Metode Dan Graphic Mechanical And Electrical Equipment (Mee) Dan Perhitungan Empiris - Tegar Prassetyo; Al Ikbal Arbi (Fakultas Teknik Universitas Persada Indonesia YAI, 2023)
Tanah Abang Blok A Wholesale Market is a modern wholesale center in Jakarta that has more than 10floors and to make it easier for visitors to carry out activities that move the first floor j another floor, a verticaltransformation is needed, namely an elevator. Elevators are needed to streamline the time, mileage, and userpower to reach the first floor to other floors in a high-rise building. So in this Tugas Akhir the author takes thetitle Analisis performance elevator case study in Pasar grosir Tanah Abang block A. The method used is to usethe method of literature, observation, and interviews so that it is hoped that the author will be able to make iteasier to analyze it. In this study, the problems that will be discussed are the carrying capacity of the elevator,the waiting time of the elevator, the power of the motor, and the number of units. From this study, the followingresults were obtained for the elevator carrying capacity of 118 people for passenger elevators and 120 people forfreight elevators, waiting times for passenger elevators for 43.4 seconds and for freight elevators for 62.9 seconds,motor power for passenger elevators of 15 KW and freight elevators of 18 KW, and the number of units as manyas 4 units for passenger elevators and as many as 3 units for freight elevators.